The Relevance of The Equality Creditors’ Principles to The Preferential, Secured, and Concurrent Creditors in the Discharge Process of The Bankruptcy Assets to Achieve Justice - et al., Winanto (International Journal of Advanced Science and Technology, 2019)
The background study of the paper entitled "The relevance of the creditors' equality principles to the preferential, secured, and concurrent creditors in the discharge process of bankruptcy assets to achieve a justice" is due to the lack of the process of the distributing bankruptcy assets to creditors. If the bankruptcy assets are insufficient for the debt amount, the distribution of the bankruptcy assets potentially causes injustice since the creditors’ force to ask the distribution based on their classes. Therefore, this paper is to find out the relevance of the creditors’ equality principles to the discharge of the bankruptcy assets to achieve justice. The principle normalization or the creditors’ equality in the laws and regulations of the bankruptcy is relevance to be a technical guideline for the curators when distributing the bankruptcy assets to achieve justice.